Rattan as a crop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Forest people in southeastern Borneo are producing both rattan used for making baskets, 'cane' furniture, etc and food by shifting cultivation without harming the environment, according to a report by Joseph Weinstock, published in...